2007
DOI: 10.1109/tpwrs.2007.901658
|View full text |Cite
|
Sign up to set email alerts
|

Fault Ride-Through of Large Wind Farms Using Series Dynamic Braking Resistors (March 2007)

Abstract: Fault ride-through (FRT) is required for large wind farms in most power systems. Fixed speed wind turbines (FSWTs) are a diminishing but significant sector in the fast-growing wind turbine (WT) market. State-of-art techniques applied to meet grid requirements for FSWT wind farms are blade pitching and dynamic reactive power compensation (RPC). Blade pitching is constrained by the onerous mechanical loads imposed on a wind turbine during rapid power restoration. Dynamic RPC is constrained by its high capital co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
140
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 223 publications
(142 citation statements)
references
References 11 publications
0
140
0
2
Order By: Relevance
“…The parameters of the current control loop and fieldweakening control loop were designed by the eigenvalue method for state-space equations, in consideration of the large inertia property of DD-WTs. In addition, excitation losses of different degrees occur in PMSG rotors as the service time of DD-WTs extends [135]. Similar to the weak magnetic principle of permanent magnets, i d is used to increase the magnetic field to realize instantaneous excitation loss or partial demagnetization for reliable operation.…”
Section: Operation Control Of Epcss In Dd-wts Under Faultsmentioning
confidence: 99%
“…The parameters of the current control loop and fieldweakening control loop were designed by the eigenvalue method for state-space equations, in consideration of the large inertia property of DD-WTs. In addition, excitation losses of different degrees occur in PMSG rotors as the service time of DD-WTs extends [135]. Similar to the weak magnetic principle of permanent magnets, i d is used to increase the magnetic field to realize instantaneous excitation loss or partial demagnetization for reliable operation.…”
Section: Operation Control Of Epcss In Dd-wts Under Faultsmentioning
confidence: 99%
“…A bridge-type fault current limiter (BFCL) has been proposed to enhance the transient stability of DFIGs, which is a promising application in an AC grid [18][19][20][21], but it only suits specific situations. A SDBR has a simple structure, which is applied in both AC and DC grids to enhance the transient stability and fault ridethrough capability of generators [22][23][24], but it cannot overcome both overcurrent and overvoltage issues and current impulse usually occurs.…”
Section: Introductionmentioning
confidence: 99%
“…At the early stage, only DC motors were used to drive pumps. Direct coupling of series, shunt, and separately exited DC motor Wind Turbine Generator pumping systems were studies [6,7]. It was found that the overall performances are totally different from those obtained when these motors are connected to a constant voltage source.…”
Section: Introductionmentioning
confidence: 99%